Материалы и конструкции теплозащиты возвращаемых космических аппаратов - Гусарова, И.А.; Манько, Т.А.; Потапов, А.М. (Вісник Українського матеріалознавчого товариства, 2016)
Heat protection tile structures of windward side reusable spacecraft made of different materials were analyzed. It was shown that a reliable thermal protection with operating temperatures up to 1100 °C which is able to withstand 100 launches with dimension-mass and cost constraints until now is not created. Directions of such thermal protection development were determined.